Pengaruh Partisipasi Manajemen Terhadap Kepatuhan, Kebenaran Laporan, Transparansi, Dan Akuntabilitas Melalui Akuntansi Instansi: Studi Pada Instansi PT X dan Lembaga/unit pemerintah wilayah Jawa Timur - Hardi Supeno; Noviansyah Rizal (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2012)
Recently, government intends to build a well-organized management in all governmen- tal divisions. Financial management given to all of them must reflect the well-organized and accountable management. To gain this government need to respond to the program application of institutional accounting system as a means to exhibits financial transpar- ency and responsibility toward society. The role of management is very important in its implementation; that is to maintain report accuracy, which is responsive, communicative, accountable, and transparent, which will create a good governmental management.